Engineering substrate promiscuity in halophilic alcohol dehydrogenase (HvADH2) by in silico design - Cassidy, Jennifer; Bruen, Larah; Rosini, Elena; Molla, Gianluca; Pollegioni, Loredano; Paradisi, Francesca (Public Library of Science, 2017)
An alcohol dehydrogenase from the halophilic archaeon Haloferax volcanii (HvADH2) has been engineered by rational design to broaden its substrate scope towards the conversion of a range of aromatic substrates, including flurbiprofenol, that is an intermediate of the non-steroidal anti-inflammatory drug, flurbiprofen. Wild-type HvADH2 showed minimal activity with flurbiprofenol (11.1 mU/mg). A homology model of HvADH2 was built and docking experiments with this substrate revealed that the biphenyl rings of flurbiprofenol formed strong interactions with residues F85 and F108, preventing its optimal binding in the active site. Mutations at position 85 however did not increase activity. Site directed mutagenesis at position F108 allowed the identification of three variants showing a significant (up to 2.3-fold) enhancement of activity towards flurbiprofenol, when compared to wild-type HvADH2. Interestingly, F108G variant did not show the classic inhibition in the presence of (R)-enantiomer when tested with rac-1-phenylethanol, underling its potential in racemic resolution of secondary alcohols.